Intensive probation: An examination of recidivism and social adjustment - Noonan, Susan B. (American journal of criminal justice, 1987)
Intensive supervision was began as an extension of regular probation for those offenders who needed closer surveillance. However, in the last decade, Intensive Supervision has been used increasingly as an alternative to incarceration in order to help alleviate the problem of overcrowding in our prisons. In the eight-year period from 1977 to 1985, the prison population of this country has increased 68 percent. In view of this, many states are using intensive supervision as one alternative to reduce commitment rates. This study examines the effectiveness of one such program called the Intensive Treatment Supervision Program which operates out of the Montgomery County Adult Probation Department, Dayton, Ohio. The performances of probationers on intensive supervision are compared to a group of probationers on regular supervision to determine whether intensive supervision, through improved service delivery, can have an impact on high risk probationers and serve as a basis for a program to divert offenders from overcrowded facilities.